2017
DOI: 10.1007/s13205-017-0610-3
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces artemisiae MCCB 248 isolated from Arctic fjord sediments has unique PKS and NRPS biosynthetic genes and produces potential new anticancer natural products

Abstract: After screening marine actinomycetes isolated from sediment samples collected from the Arctic fjord Kongsfjorden for potential anticancer activity, an isolate identified as Streptomyces artemisiae MCCB 248 exhibited promising results against the NCI-H460 human lung cancer cell line. H460 cells treated with the ethyl acetate extract of strain MCCB 248 and stained with Hoechst 33342 showed clear signs of apoptosis, including shrinkage of the cell nucleus, DNA fragmentation and chromatin condensation. Further to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The results were similar to the studies of Sharma et al ( 2016 ) and Passari et al ( 2015 ), and it was shown that actinomycetes possessing antifungal activity were positive for the presence of both of these two biosynthetic pathway genes in their genomes. The presence of genes encoding PKS-I and NRPS in strain CB-75 is indicative of the possibility that it can produce bioactive secondary metabolites belonging to these two classes of natural products, or a hybrid of both (Dhaneesha et al, 2017 ). Relatively low sequence similarity of the PKS-I gene sequences (84%) with those available in GenBank is indicative of the possibility that novel compounds are produced by Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%
“…The results were similar to the studies of Sharma et al ( 2016 ) and Passari et al ( 2015 ), and it was shown that actinomycetes possessing antifungal activity were positive for the presence of both of these two biosynthetic pathway genes in their genomes. The presence of genes encoding PKS-I and NRPS in strain CB-75 is indicative of the possibility that it can produce bioactive secondary metabolites belonging to these two classes of natural products, or a hybrid of both (Dhaneesha et al, 2017 ). Relatively low sequence similarity of the PKS-I gene sequences (84%) with those available in GenBank is indicative of the possibility that novel compounds are produced by Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%
“…For more than 40 years, small organic molecules (<3,000 Daltons) derived from microbes and plants have been used as chemotherapy agents for cancer (Kinghorn et al, 2009). The Streptomyces bacteria are the main source of medicinal compounds derived from microbes for nearly 80% of drugs, especially antibiotics (Weber et al, 2015) and anticancer agents (Dhaneesha et al, 2017;Nguyen et al, 2020). In our previous research, we discovered a marine bacterium, Streptomyces sp.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the rich microbial diversity and unique selective pressures experienced by the Arctic microbiome, we hypothesize that this extreme environment has potential for harboring novel antibacterial secondary metabolites. Previous bioprospecting studies conducted in polar cryohabitats have successfully identified microbial isolates expressing new natural products and encoding unknown secondary metabolite BGCs (Mitova et al, 2005; Tedesco et al, 2016; Dhaneesha et al, 2017). One such example includes the discovery of Streptomyces artemisiae MCCB 248 isolated from sediments in the Arctic fjord Kongsfjorden.…”
Section: Introductionmentioning
confidence: 99%
“…One such example includes the discovery of Streptomyces artemisiae MCCB 248 isolated from sediments in the Arctic fjord Kongsfjorden. This isolate was shown to produce secondary metabolites with anticancer properties and was found to encode unique polyketide synthetase (PKS) and non-ribosomal peptide (NRP) genes (Dhaneesha et al, 2017). Isolating secondary-metabolite-producing microbes from Arctic environments has the additional benefit of yielding strains with inhibitory activity at cold temperatures.…”
Section: Introductionmentioning
confidence: 99%